Great apes show altercentric influences when confronted with conflicting beliefs - Marie Padberg; Daniel Hanus; Daniel Haun (Animal Behaviour, 2025)

Social attention increases object memory in adult but not younger great apes - Marie Padberg; Daniel Hanus; Maleen Thiele; Danyi Wang; Lauren H. Howard; Charlotte Grosse Wiesmann; Luke Maurits; Johanna Eckert; Daniel B.M. Haun (Animal Behaviour, 2025)

Chimpanzees use observed temporal directionality to learn novel causal relations - Claudio Tennie; Christoph J. Völter; Victoria Vonau; Daniel Hanus; Josep Call; Michael Tomasello (Primates, 2019)
We investigated whether chimpanzees use the temporal sequence of external events to determine causation. Seventeen chimpanzees ( Pan troglodytes ) witnessed a human experimenter press a button in two different conditions. When she pressed the “causal button” the delivery of juice and a sound immediately followed (cause-then-effect). In contrast, she pressed the “non-causal button” only after the delivery of juice and sound (effect-then-cause). When given the opportunity to produce the desired juice delivery themselves, the chimpanzees preferentially pressed the causal button, i.e., the one that preceded the effect. Importantly, they did so in their first test trial and even though both buttons were equally associated with juice delivery. This outcome suggests that chimpanzees, like human children, do not rely solely on their own actions to make use of novel causal relations, but they can learn causal sequences based on observation alone. We discuss these findings in relation to the literature on causal inferences as well as associative learning.